Implementation of Online Attendance to Improve Discipline of Research and Development Agency Employees at the Medan Mayor's Office - Fira Nafisah; Andri Soemitra (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
The Research and Development Agency is a supporting element for government affairs within the scope of research and development. In carrying out these government duties, the employees of the Research and Development Agency of the Medan Mayor's Office are required to have high discipline as a form of implementing good performance. In order to create human resources, especially in this case employees who have good performance in terms of discipline, it is necessary to apply online attendance. This study contains information regarding the implementation of online attendance to improve the discipline of the Research and Development Agency employees at the Medan Mayor's Office. This research will also provide further explanations regarding the implementation of online attendance, describing the performance of the Research and Development Agency employees at the Medan Mayor's Office and how the implementation of online attendance relates to the discipline of the Research and Development Agency employees at the Medan Mayor's Office. This research is a descriptive survey which will later describe the implementation of online attendance to improve the discipline of the Research and Development Agency employees at the Medan Mayor's Office. The results show that the implementation of online attendance to improve the discipline of the Research and Development Agency employees at the Medan Mayor's Office is an innovation that really describes the improvement of appropriate technology. The online attendance is also very helpful in improving the discipline of the Research and Development Agency employees at the Medan Mayor's Office. The obstacles that are still being faced are that there are still some civil servants who have not been able to use technology properly, especially in the implementation of the Research and Development Agency's online attendance at the Medan Mayor's Office.